Type 2 responses determine skin rash during recombinant interleukin-2 therapy - Charline Sommer; Vanessa Neuhaus; Patricia Gogesch; Thierry Flandre; Susann Dehmel; Katherina Sewald (Journal of Immunotoxicology)
The skin is the organ most often affected by adverse drug reactions. Although these cutaneous adverse drug reactions (CADRs) often are mild, they represent a major burden for patients. One of the drugs inducing CADRs is aldesleukin, a recombinant interleukin-2 (recIL-2) originally approved to treat malignant melanoma and metastatic renal cell carcinoma which frequently led to skin rashes when applied in high doses for anti-cancer therapy. Skin rashes and other side effects, together with poor efficacy led to a drawback of the therapeutic, but modified recIL-2 molecules are on the rise to treat both cancer and inflammatory diseases such as autoimmunity. Still, pathophysiological mechanisms of recIL-2-induced skin rashes are not understood. In the study reported here, a hypothetical literature-based immune-related adverse outcome pathway (irAOP) was developed to identify possible key cells and molecules in recIL-2-induced skin rash. Using this approach, a hypothesis was formed that the induced immune response predominantly is Type 2-driven by T-helper and innate lymphoid cells, leading to the occurrence of cutaneous side effects during recIL-2 therapy. This paper further discusses mechanisms beyond the proposed irAOP which might add to the pathology but currently are less-studied. Together, this hypothetic irAOP forms a basis to clarify possible cellular and molecular interactions leading to recIL-2-induced skin rash. This might be used to adapt existing or develop new test systems to help predict and prevent cutaneous side effects in future IL-2-based or similar therapies.